Argumentation as troubleshooting in the neocorporativistic speech of venezuelan policies (1989-1994). Critical analysis. - Pineda, Alicia (Telos: Revista de Estudios Interdisciplinarios en Ciencias Sociales, 2024)
The discourse of Development Plans in Venezuela (1989-1994) is critically analyzed in order to unveil the argumentative strategies that ideologically justify the policies formulated by the International Monetary Fund (IMF) in the context of applying the neocorporativist model of the new economy neoliberal The theoretical framework basically contemplates the authors: Maniglio (2017), White (1999), Habermas (1999), Beaugrande and Dressler (1997), Martín y Whittaker (1998), Charaudeau (1992) y Pottier (1992). The methodology used combines the design of argumentative structures and critical discourse analysis with the “round trip” abductive process between theory and practice (Wodak, 2003: 109). The results are: construction of argumentative relationships and identification of resources and strategies used as legitimation / delegitimization operations. It concludes: 1) the evaluative resources, assessments and axiological modalities used in practical, normative and ethical judgments are fundamentally the basis of the argumentative strategies that justify the link between problems and solutions, and in this sense, these strategies persuade about “being "And the duty" of policies. 2) the arguments presented are increasingly prescriptive and with high coercive discursive levels, both explicit and implicit.